(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
Greece has recently amended its legislation on medically assisted reproduction, extending the conditions under which surrogacy can be practiced and introducing one of the most liberalised regime of surrogacy in Europe . The aim of this paper is to investigate, in a comparative perspective, the consequences of these new provisions, taking also into account the Italian legal framework, considered one of the most restrictive at the European level – in the perspective of the most recent developments of the European Court of Human Rights’ case law. In particular, the paper focuses on the problem of the guarantee of the best interests of the child born through surrogacy and on the legal issues related to the phenomenon of cross-border surrogacy.